An interactive sketch-based CAD interface realizing geometrical and topological editing across multiple objects based on fuzzy logic. (April 2022) - Ito, Tomohiko; Kaneko, Teruyoshi; Tanaka, Yoshiki; Saga, Sato
Abstract: With the widespread use of digital pen tablets and touch displays, sketch-based interactive computer-aided design (CAD) user interfaces have attracted considerable attention. In an existing interface called the Sketch Input Tracer (SKIT), however, the editing operation performed via an over-sketching stroke can target only a single geometric object at any given time. To overcome this limitation, in this study, we propose a new general-purpose sketch-based interface developed for use in two-dimensional CAD systems. In the proposed interface, a sketch-based editing operation can simultaneously modify the geometry and topology of multiple geometric objects via over-sketching. The interface was developed based on the fuzzy logic-based strategy of SKIT. With this interface, a user can draw in a creative manner; for example, they can begin with a rough sketch and progressively create a detailed design through repeated over-sketches. The results of experiments conducted demonstrate that experts can control the proposed interactive drawing interface and beginners can habituate to controlling it. Graphical abstract: Highlights: A new general-purpose sketch-based interface for 2D CAD systems is proposed. The interface is based on the SKIT fuzzy-logic strategy. An editing operation via over-sketching can modify multiple geometric objects. Users can repeatedly over-sketch on a rough drawing to obtain a detailed design. Adequate controllability by trained users of the interface is shown quantitatively.